Characterization of the stability of semiconductor lasers with delayed feedback according to the Lang-Kobayashi model - Gallas, Jason A.; Junges, Leandro; Pöschel, Thorsten (European Physical Journal D, 2013)
We report a numerical characterization of the stability of semiconductor lasers with delayed feedback under the simultaneous variation of the delay time τ and the pump current P. Changes in the number of External Cavity Modes are studied as a function of the delay time while the Regular Pulse Package regime is characterized as a function of the pump current. In addition, we describe some remarkable structures observed in the τ ×P control plane, delimiting where these and other complex regimes of laser operation exist.